Phenylalanine loading in pediatric patients with dopa-responsive dystonia: revised test protocol and pediatric cutoff values - Opladen, Thomas; Okun, Jürgen G.; Burgard, Peter; Blau, Nenad; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2010)
Objectives The objectives of this study were to determine the value of phenylalanine (Phe) loading for diagnosing dopa-responsive dystonia (DRD) in children. Methods We investigated orally administered Phe loading tests (100 mg/kg) in seven patients with confirmed DRD and 17 pediatric patients with clinically suspected but excluded DRD. Results of Phe, tyrosine (Tyr), and biopterin from plasma and dried blood spot (DBS) analyses were correlated, and pediatric cutoff values established. Results The peak Phe concentration following a Phe load in the pediatric DRD population is lower than reported in adults. By using adult cutoff values and either Phe/Try ratios or biopterin concentrations only, false positive and false negative results are frequent. Only the combined analysis of the Phe/Tyr ratio and biopterin concentration is reliable in children. In children with DRD, dried blood Phe/Tyr ratio exceeded 4.6 (plasma Phe/Tyr ratio >5.4) after 2 h and biopterin concentration in dried blood remained below 16.2 nmol/L (plasma biopterin <14 nmol/L) 1 h after Phe challenge. Conclusions Phe loading is a useful tool for diagnosing DRD in children. Test duration can be reduced to only 2 h, and specific pediatric cutoff values need to be applied. Simultaneous measurements of the Phe/Tyr ratio and biopterin in plasma or DBS are essential in pediatric patients.
Gesehen am 16.06.2023